Role of magnetic resonance imaging in diagnosis and grading of perianal fistulas - Saurabh S Kakani (Manipal College of Medical Sciences, Pokhara, 2021)
Background: Fistula-in-ano can be defined as a hollow tract or cavity which is lined by granulation tissue. In case of fistula-in-ano, one end of this fistula opens in the anal canal whereas the other end is located in perianal area. Fistula-in-ano can considerably affect quality of life of an individual because of perianal discharge of blood and pus. Imaging of these fistulas is an important part of management and MR imaging is important in assessing relationship between the fistulous tract and sphincter muscles. Moreover, MR imaging can reliably demonstrate transmural inflammation, secondary tracts/ramifications, and abscesses which cannot be diagnosed on the basis of conventional fistulography.